Mosque-Based Disaster-Resistant Family Improvement Training in Sukopuro Village, Malang District - P. Mochammad Rozikin; Wiwik Utami; Kustyarini; Klara Kumalasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Sukopuro Village is one of the areas in Jabung District, Malang Regency, which consists of 13 RWs (Rukun Warga) and 53 RTs (Rukun Tetangga). In the last two years, almost all nations of the world, including Indonesia, have experienced the COVID-19 pandemic, according to data from the Indonesian Ministry of Health, starting from the announcement of President Joko Widodo's first case on March 2 2020, a total of 6,046,467 cases were recorded with 5,882,062 recovered cases. and cases of death amounted to 156,240. Three important points of the proposed program Disaster resilient families (Katana), namely: (1) Katana can become a pillar of community and family resilience against disaster risk; (2) Katana must involve vulnerable groups, children, pregnant women, the elderly and women; and (3) Katana utilizes the closest community institutions that already exist in their environment.